Dietary histidine requirement of juvenile blunt snout bream (Megalobrama amblycephala). (5th January 2018) - Wilson‐Arop, O.‐M.; Liang, H.; Ge, X.; Ren, M.; Habte‐Tsion, H.‐M.; Ji, K.
Abstract: An eight‐week feeding trial was conducted to determine the dietary histidine requirement of juvenile blunt snout bream. The results showed that final body weight, weight gain rate and specific growth rate significantly increased with increasing dietary histidine levels up to 9.9 g/kg ( p < .05) and decreased gradually thereafter, while feed conversion ratio showed a converse trend. The survival rate, condition factor, viscerosomatic and hepatosomatic index were not significantly affected by the graded dietary histidine levels ( p > .05). About 9.9 g/kg dietary histidine level significantly improved whole‐body protein and lowered moisture content. The contents of plasma total protein, cholesterol, urea and triglyceride levels were not significantly affected by dietary histidine levels. About 9.9 g/kg dietary histidine level significantly upregulated target of rapamycin and insulin‐like growth factor mRNA levels ( p < .05), and 12.1 g/kg and 14.2 g/kg dietary histidine levels significantly upregulated eukaryotic translation initiation factor 4E‐binding protein 2 and ribosomal protein S6 kinase‐polypeptide 1 mRNA levels ( p < .05). Based on second‐degree polynomial regression analysis of weight gain rate, and specific growth rate against dietary histidine levels, the dietary histidine requirement for juvenile blunt snout bream was estimated to be 11.2 g/kg of diet, corresponding to 36.1 g/kg of dietary protein.